An inquiry into how Inter Press Service Africa makes alternative news from the Global South - Chiwota, Elijah (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
An inquiry into how Inter Press Service (IPS) Africa makes alternative news from the Global South, is a study of a news agency that seeks to reverse the flows of information which predominantly comes from the Global North and by doing so carries the interests of the Global North (Boyd-Barrett, 2003). IPS was founded in 1964 by an international co-operative of journalists in the aftermath of the Cuban Revolution. At the same time, struggles for decolonization were at their peak in Africa and Asia. IPS promotes journalism for South-South co-operation and horizontal communication -- ideas that coincidentally found resonance in the debates for the New World Information and Communication Order (NWICO) that took place under the auspices of the United Nations Scientific and Cultural Organization (UNESCO) in 1980 (MacBride, 1980). As a regional centre of the IPS and a news agency of the Global South, IPS Africa is an alternative to international news agencies whose reports on Africa are characterised by representations of the other with a narrow focus on natural disasters, poverty, disease, and conflict. To counter this, IPS Africa developed alternative ways of news making from the Global South that focuses on highlighting the United Nations Sustainable Development Goals (SDGs) as one of the strategies to end poverty and promote sustainable development and to recognize the centrality of global partnerships for sustainable development. IPS African stories are written by local journalists who are familiar with the context under which they report. These stories can be described using the lenses of radical media content. IPS Africa is a not-for-profit news agency that makes news based on its organizational themes. Some of the stories emanate from reporters and editors who investigate development issues in their communities and link these to global events and developments. The study draws on Atton (2001) model of alternative and radical media to identify characteristics that include radical content and news values. A social realist approach is used in the study and the qualitative methods used are the analysis of documents, in-depth interviews, and textual analysis. The findings conclude that although a non-profit, IPS Africa can be described as a hybrid media organization in that it is a traditional news agency, with a management structure with board members, who contract freelance journalists to write copy. However, more meaning is found in the radical content of its stories. Despite being firmly rooted in its mission of "telling Africa's untold stories," the news agency has insufficient human and financial resources. Consequently, it faces sustainability and viability problems because of its over-reliance on external support through donor funds.
Keywords: Inter Press Service -- Regional Centre for Africa; Workshop on the New World Information and Communication Order (1980 : Geneva, Switzerland); Sustainable Development Goals Fund; Mass media -- Political aspects; Radicalism and the press; Mass media and globalization; Hegemony -- Political aspects; Counter hegemony